Odpowiedź :
Odpowiedź:
a) 2*x +5= - 3
2x+5= - 3
2x= - 3 -5
2x= - 8 /:2
x= - 4
b) - 7 *a -3 = 11
-7a -3=11
-7a= 11+3
-7a = 14 /:(-7)
a= - 2
c) 5+6*x =23
5+6x= 23
6x= 23 -5
6x= 18 /:6
x=3
a) 7*x-5= 4
7x-5=4
7x= 4+5
7x=9 /:7
x= 9/7= 1 i 2/7
b) 2*a - 0,2= 11
2a- 0,2= 11
2a= 11 +0,2
2a= 11,2 /:2
a= 5,6
c) 3/5 +6*x= 7,6
3/5+ 6x= 7,6
6x= 7,6- 0,6
6 x= 7 /:6
x= 1 i 1/6
Szczegółowe wyjaśnienie:
Odpowiedź:
A)x=-3-2*-5
x=-3-10
x=-13
b)a=11+7+3
x=21
C)x=23-5*6
x=23-30
x=-7
A)x=4-7*5
x=4-35
x=-31
B) a=11-2*0.2
a=11-0.4
x=7,6-3/5-6
x=7-6
x=1
Szczegółowe wyjaśnienie: